Finite element analyses of lateral condyle fracture fixation in paediatrics regarding configuration of Kirschner-wire - Jeon, Sangbin; Ahn, Wooyeol; Oh, Jongbeom; Chung, Jaiwoo; Choi, Junwon; Lee, Soonchul (BMC Musculoskeletal Disorders, 2022)
Background: This study aimed to discover the most stable outcome among different Kirschner-wire (K-wire) configurations for fixation of a lateral condyle fracture (Milch type II) in different loads of stress by using finite element analyses (FEA). Methods: The right humerus of a 6-year-old boy with a lateral condyle fracture (Milch type II), was modelled with a computer aided engineering. Using FEA, peak von Mises stress and stiffness were evaluated first for a single K-wire fixation by varying the angle (0, 5, 10, 15, 20, 25, 30 degrees). Then, based on the single K-wire result, assessment of peak von Mises stress and stiffness were evaluated via FEA for two- or three-wire fixation under various configurations (two convergent, two parallel, three divergent). Results: Single K-wire fixation by 5 and 25 degrees had the lowest peak von Mises stress. The fracture site showed higher stiffness at 0, 5 and 15 degrees. Considering the collected results and clinical situation, 5 degree K-wire was selected for the FEA of multiple K-wire fixation. For multiple K-wire fixation, three divergent (5–20-35 degrees) K-wires showed better stability, both in peak von Mises stress and stiffness, than any two-K-wire configurations. Among two K-wire fixations, two divergent (5–50 degrees) K-wires provided the lowest von Mises stress in varus and valgus while two divergent (5–65 degrees) K-wires showed better results in flexion, extension, internal and external rotation, and both configurations showed similar results in stiffness. Conclusions: We successfully created a paediatric lateral condyle fracture (Milch type II) model which was used to conduct FEA on different K-wire configurations to achieve stability of the fracture. Our results show that an initial K-wire inserted at 5 degrees, followed by the insertion of a second divergent wire at either 45 or 60 degrees provides the most stability in two K-wire fixations in this type of fracture repair.
Keywords: Bone Wires; Child; Finite Element Analysis; Fracture Fixation; Fracture Fixation, Internal; Humans; Humeral Fractures; Humerus; Male; Pediatrics; Finite element analyses; Fixation; Kirschner-wire; Lateral condyle fracture